(untitled) (Per Musi, 2023)
The life and work of North American composer Stuart Saunders Smith (1948) have shown features reminiscent of the 19th century philosophical movement known as New England Transcendentalism. Here I discuss how ideas divulged by Transcendentalism and transcendentalist philosophies, in particular oneness, freethinking, anti-materialism, anti-technologism, and silence reflect in Smith’s life stances and compositional process. Based on a belief that oneness binds all living beings via a universal soul, Smith seeks to symbolically unify composer, performer, and audience through the use of silence and a compositional technique called co-existence. In turn, anti-materialism and anti-technologism manifest musically in his frugal use of instrumentation, and in his refusal to write for electronics while evoking naturalistic themes, respectively.